The Impact of Artificial Intelligence on the Sustainable Development Performance of Chinese Manufacturing Enterprises - Chaobo Zhou (Systems)
As a major driving force in the current technological revolution, artificial intelligence (AI) has significantly accelerated the intelligence, automation, and informatization of enterprises, thereby inevitably influencing the sustainable development performance (SDP) of manufacturing enterprises. This study takes the “Next-Generation AI Innovation Pilot Zone” policy as a case study and utilizes a multi-period difference-in-differences (DID) model and machine learning techniques to investigate the impact of AI on the SDP of Chinese manufacturing enterprises. The findings indicate that AI contributes to improving the SDP of manufacturing firms. The mechanism analysis reveals that AI enhances SDP via a green innovation effect, cost-saving effect, and digital transformation effect. The moderation analysis further shows that the CEO duality inhibits the positive impact of AI on SDP. The heterogeneity results based on the GRF model indicate that the positive relationship between AI and SDP is pronounced in state-owned enterprises and heavily polluting firms. This study not only enriches the literature on the micro-level environmental effects of AI but also provides valuable insights for governments and businesses seeking to improve SDP.